2021
DOI: 10.4317/jced.58781
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of a novel neem paste against cariogenic bacteria

Abstract: Background Dental caries is a major oral health problem, which associates with cariogenic bacteria. Streptococcus mutans and Lactobacillus acidophilus are facultative anaerobic bacteria that are found in tooth decay. Accordingly, neem leaf extract was developed due to its great anti-microbial property against many bacteria. The aim of this study was to determine anti-cariogenic properties of neem leaf extract in a novel paste preparation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Nine out of thirty-five compounds were phytol, α-capaene, α-humulene, β-caryophyllene, δ-cadinene, carvone, aromadendrene, octadeamethyl-cyclononasiloxane, and β-bourbonene. According to previous studies, these compounds possessed the anti-proliferative property 13 - 21 (see detail in Discussion). One compound, β-caryophyllene, possessed mineralization induction property 22 .…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Nine out of thirty-five compounds were phytol, α-capaene, α-humulene, β-caryophyllene, δ-cadinene, carvone, aromadendrene, octadeamethyl-cyclononasiloxane, and β-bourbonene. According to previous studies, these compounds possessed the anti-proliferative property 13 - 21 (see detail in Discussion). One compound, β-caryophyllene, possessed mineralization induction property 22 .…”
Section: Resultsmentioning
confidence: 64%
“…GC-MS allowed the detection of various substance groups including sesquiterpenoids, diterpenes, terpenoid, organoheterosilanes, trialkylamines, ethylamines, fatty acid, amino acid, carboxylic acids, hydrocarbon, benzofuran, barbiturate, glucoside and furanoid. From the ethanolic neem extract, 35 compounds were identified 13 . Nine out of thirty-five compounds were phytol, α-capaene, α-humulene, β-caryophyllene, δ-cadinene, carvone, aromadendrene, octadeamethyl-cyclononasiloxane, and β-bourbonene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterocyclic compounds, including polysaccharides and carbohydrates, have many active centers and electronegative atoms. All active groups, electronegative atoms, polysaccharide compounds, carbohydrates, and oxygen atoms, in the case of the ionic state, have partial ionization that can adsorb the ionized lead element in solution, and this adsorption is a chemical as well as physical adsorption 90 . The coordination tendency of aromatic electrons to donate groups involving hydroxyl, ether, and phenyl groups is much superior to that in corresponding aliphatic groups.…”
Section: Discussionmentioning
confidence: 99%
“…Additional biologically relevant studies may be able to provide even more evidence for the use of neem in dentistry in combination with, or as an alternative to, antimicrobials already used in the field. Of note, several studies have already suggested that neem extracts have similar levels of activity as chlorhexidine or hypochlorite (typical components of oral washes) against plaque, gingivitis, and pain in vivo ( Jalaluddin et al, 2017 ; Hosny et al, 2021 ) and against biofilm-forming bacteria (e.g., Streptococcus viridans, Porphyromonas gingivalis, and S. aureus ) and C. albicans in vitro or ex vivo ( Joy Sinha et al, 2015 ; Anand et al, 2016 ; Kankariya et al, 2016 ; Heyman et al, 2017 ; Andonissamy et al, 2019 ; Bansal et al, 2019 ; Tasanarong et al, 2021 ). Another human pathogen that causes plaque and other biofilm-related diseases in the body, E. faecalis , is also just as susceptible to various neem extracts as it is to chlorhexidine in vitro ( Chandrappa et al, 2015 ; Mustafa, 2016 ; Bhardwaj et al, 2017 ; Joy Sinha et al, 2017 ).…”
Section: Antibacterial Evidencementioning
confidence: 99%